Spline interpolation

From Wikipedia, the free encyclopedia
Jump to: navigation, search

In the mathematical field of numerical analysis, spline interpolation is a form of interpolation where the interpolant is a special type of piecewise polynomial called a spline. Spline interpolation is often preferred over polynomial interpolation because the interpolation error can be made small even when using low degree polynomials for the spline. Spline interpolation avoids the problem of Runge's phenomenon, in which oscillation can occur between points when interpolating using high degree polynomials.

Introduction[edit]

Originally, spline was a term for elastic rulers that were bent to pass through a number of predefined points ("knots"). These were used to make technical drawings for shipbuilding and construction by hand, as illustrated by Figure 1.

Figure 1: Interpolation with cubic splines between eight points. Hand-drawn technical drawings were made for shipbuilding etc. using flexible rulers that were bent to follow pre-defined points

The approach to mathematically model the shape of such elastic rulers fixed by n+1 knots (x_i,y_i)\quad i=0,1,\dotsc,n is to interpolate between all the pairs of knots (x_{i-1}\ ,\ y_{i-1}) and (x_i\ ,\ y_i) with polynomials y=q_i(x), \quad i=1,2,\dotsc,n.

The curvature of a curve

y=f(x)

is

\kappa= \frac{y''}{(1+y'^2)^{3/2}}

As the spline will take a shape that minimizes the bending (under the constraint of passing through all knots) both y' and y'' will be continuous everywhere and at the knots. To achieve this one must have that

q'_i(x_i) = q'_{i+1}(x_i)

and that

q''_i(x_i) = q''_{i+1}(x_i)

for all i, 1 \le i \le n-1. This can only be achieved if polynomials of degree 3 or higher are used. The classical approach is to use polynomials of degree 3 — the case of cubic splines.

Algorithm to find the interpolating cubic spline[edit]

A third order polynomial q(x) for which

q(x_1)=y_1
q(x_2)=y_2
q'(x_1)=k_1
q'(x_2)=k_2

can be written in the symmetrical form

q\ =\ (1-t)\ y_1 +\ t\ y_2\ +\ t\ (1-t)\ (a\ (1-t) + b\ t)

 

 

 

 

(1)

where

t=\tfrac{x-x_1}{x_2-x_1}

 

 

 

 

(2)

and

a= \ k_1 (x_2 - x_1)-(y_2 - y_1),

 

 

 

 

(3)

b=-k_2 (x_2 - x_1)+(y_2 - y_1).

 

 

 

 

(4)

As q'= \tfrac{d q}{d x} = \tfrac{d q}{d t} \ \tfrac{d t}{d x} = \tfrac{d q}{d t} \ \tfrac{1}{x_2-x_1} one gets that:

q'\ =\frac {y_2-y_1}{x_2-x_1} +(1-2t)\ \frac {a\ (1-t) + b\ t}{x_2-x_1}\  +\ \ t\ (1-t)\ \frac {b-a}{x_2-x_1},

 

 

 

 

(5)

q''=2\frac {b-2a+(a-b)3t}{{(x_2-x_1)}^2}.

 

 

 

 

(6)

Setting x = x1 and x = x2 respectively in equations (5) and (6) one gets from (2) that indeed first derivatives q'(x1) = k1 and q'(x2) = k2 and also second derivatives

q''(x_1)=2\frac {b-2a}{{(x_2-x_1)}^2}

 

 

 

 

(7)

q''(x_2)=2\frac {a-2b}{{(x_2-x_1)}^2}

 

 

 

 

(8)

If now (xi, yi) where i = 0, 1, ... , n are n+1 points and

q_i\ =\ (1-t)\ y_{i-1} +\ t\ y_i\ +\ t\ (1-t)\ (a_i\ (1-t) + b_i\ t)

 

 

 

 

(9)

where i = 1, 2, ..., n and t=\tfrac{x-x_{i-1} }{ x_{i}-x_{i-1} } are n third degree polynomials interpolating y in the interval x i-1xxi for i = 1,... , n such that q'i (xi) = q' i+1 (xi) for i = 1, ... , n-1 then the n polynomials together define a differentiable function in the interval x0xxn and

a_i=k_{i-1}(x_i-x_{i-1})-(y_i - y_{i-1})

 

 

 

 

(10)

b_i=-k_i(x_i-x_{i-1})+(y_i - y_{i-1})

 

 

 

 

(11)

for i = 1, ..., n where

k_0=q_1'(x_0)

 

 

 

 

(12)

k_i=q_i'(x_i)=q_{i+1}'(x_i) \quad i=1,\dotsc ,n-1

 

 

 

 

(13)

k_n=q_n'(x_n)

 

 

 

 

(14)

If the sequence k0, k1, ..., kn is such that in addition q"i(xi) = q"i+1(xi) for i = 1, ..., n-1 the resulting function will even have a continuous second derivative.

From (7), (8), (10) and (11) follows that this is the case if and only if

\frac {k_{i-1}}{x_i-x_{i-1}} + \left(\frac {1}{x_i-x_{i-1}}+ \frac {1}{{x_{i+1}-x_i}}\right)\ 2k_i+
\frac {k_{i+1}}{{x_{i+1}-x_i}} =
   3\ \left(\frac {y_i - y_{i-1}}{{(x_i-x_{i-1})}^2}+\frac {y_{i+1} - y_i}{{(x_{i+1}-x_i)}^2}\right)

 

 

 

 

(15)

for i = 1, ..., n-1. The relations (15) are n-1 linear equations for the n+1 values k0, k1, ..., kn.

For the elastic rulers being the model for the spline interpolation one has that to the left of the left-most "knot" and to the right of the right-most "knot" the ruler can move freely and will therefore take the form of a straight line with q" = 0 . As q" should be a continuous function of x one gets that for "Natural Splines" one in addition to the n-1 linear equations (15) should have that

q''_1(x_0)\ =2\ \frac {3(y_1 - y_0)-(k_1+2k_0)(x_1-x_0)}{{(x_1-x_0)}^2}=0,
q''_n(x_n)\ =-2\ \frac {3(y_n - y_{n-1})-(2k_n+k_{n-1})(x_n-x_{n-1})}{{(x_n-x_{n-1})}^2}=0,

i.e. that

\frac{2}{x_1-x_0} k_0\ +\frac{1}{x_1-x_0}k_1 = 3\ \frac{y_1-y_0}{(x_1-x_0)^2},

 

 

 

 

(16)

\frac{1}{x_n-x_{n-1}}k_{n-1}\ +\frac{2}{x_n-x_{n-1}}k_n = 3\ \frac{y_n-y_{n-1}}{(x_n-x_{n-1})^2}.

 

 

 

 

(17)

Eventually, (15) together with (16) and (17) constitute n+1 linear equations that uniquely define the n+1 parameters k0, k1, ..., kn.

Example[edit]

Figure 2: Interpolation with cubic "natural" splines between three points.

In case of three points the values for k_0,k_1,k_2 are found by solving the tridiagonal linear equation system


\begin{bmatrix}
a_{11} & a_{12} & 0       \\
a_{21} & a_{22} & a_{23}  \\
0      & a_{32} & a_{33}  \\
\end{bmatrix}
\begin{bmatrix}
k_0 \\
k_1 \\
k_2 \\
\end{bmatrix}
=
\begin{bmatrix}
b_1 \\
b_2 \\
b_3 \\
\end{bmatrix}

with

a_{11}=\frac{2}{x_1-x_0}
a_{12}=\frac{1}{x_1-x_0}
a_{21}=\frac{1}{x_1-x_0}
a_{22}=2\ \left(\frac {1}{x_1-x_0}+ \frac {1}{{x_2-x_1}}\right)
a_{23}=\frac {1}{{x_2-x_1}}
a_{32}=\frac{1}{x_2-x_1}
a_{33}=\frac{2}{x_2-x_1}
b_1=3\ \frac{y_1-y_0}{(x_1-x_0)^2}
b_2=3\ \left(\frac {y_1 - y_0}{{(x_1-x_0)}^2}+\frac {y_2 - y_1}{{(x_2-x_1)}^2}\right)
b_3=3\ \frac{y_2-y_1}{(x_2-x_1)^2}

For the three points

(-1,0.5)\ ,\ (0,0)\ ,\ (3,3)

one gets that

k_0=-0.6875\ ,\ k_1=-0.1250\ ,\ k_2=1.5625

and from (10) and (11) that

a_1= k_0(x_1-x_0)-(y_1 - y_0)=-0.1875
b_1=-k_1(x_1-x_0)+(y_1 - y_0)=-0.3750
a_2= k_1(x_2-x_1)-(y_2 - y_1)=-3.3750
b_2=-k_2(x_2-x_1)+(y_2 - y_1)=-1.6875

In Figure 2 the spline function consisting of the two cubic polynomials q_1(x) and q_2(x) given by (9) is displayed

See also[edit]

External links[edit]